Design of Self-Assessment Scale to Accreditation Standards - الشمري زهرة عبدمحمد (Journal of Economics and Administrative Sciences, 2014)
The process of self-assessment plays a key role in achieving quality educational institutions (college, department or program academic particular), because the assessment process provides reviews of the effectiveness of the criteria used in the enterprise, especially in the field of teaching and learning, and is result self-assessment providing self-assessment report. The self- assessment can be performed at different levels (college, academic department, Master, Ph.D. program, or courses). The importance of the research focused on to provide a measure of self-assessment helps profile officials in the implementation of the assessment process are clear and precise and fast, and to provide them to measure the availability requirements of the accreditation standards that have been adopted in their institutions. The research aimed to provide an integrated measure of the implementation of the self-assessment process included a structural measure of five Items (scale levels, design self-assessment checklist for standards accreditation, documents and indicators used to verify the application of good practices, the structure of the self- assessment report, the description improvement plan). The research relied on the academic curriculum, its relevance to the object, and the objective of the research. The research found that on each of the management of the program or institution identified with appropriate accreditation standards for academic competence to do the implementation of the self-assessment process, which must be characterized unrivaled. It should deal with the program in all fields, facilities, and services, and administrative processes to identify the strengths and weaknesses, opportunities and risks and limitations in the educational institution or in the academic program. The research recommends the formation of a self- assessment committee within the college structure of quality committee in the department, so as to implement the self-assessment process using a self-assessment scale proposed.